Determination of ultra-trace catecholamines based on hot electron-induced cathodic electrochemiluminescence at a naturally oxide-covered tantalum electrode. Issue 20 (9th February 2016) - Chen, Xiao-Yan; Zheng, Rui-Juan; Ren, Ling-Qing; Sun, Jian-Jun
Abstract : A naturally oxide-covered tantalum electrode is firstly used in the detection of ultra-trace catecholamines based on hot electron-induced cathodic electrochemiluminescence with extremely low background, excellent sensitivity and perfect stability. Abstract : Naturally oxide-covered tantalum electrodes (Ta/Ta2 O5 ) are first used in the determination of ultra-trace catecholamines based on hot electron-induced cathodic electrochemiluminescence. Under natural conditions, an oxide film can be formed on the surface of tantalum electrode, at which the quenching effect of catecholamines on the hot electron-induced cathodic electrochemiluminescence (cathodic ECL) of luminol is found. Based on this quenching effect, detection of ultra-trace catecholamines is established. No previous anthropogenic modification of the electrode and no derivatization of the catecholamines are required before determination. Under the optimum conditions, the quench ratio is linearly increased with the logarithm of the concentration of epinephrine, dopamine and norepinephrine in the range of 2.0 × 10 −8 mol L −1 to 2.0 × 10 −6 mol L −1, 8.0 × 10 −9 mol L −1 to 4.0 × 10 −7 mol L −1 and 8.0 × 10 −9 mol L −1 to 8.0 × 10 −7 mol L −1 with the limit of detection (LOD) of 5.5 × 10 −9 mol L −1 to 7.8 × 10 −10 mol L −1 and 8.2 × 10 −10 mol L −1, respectively.